Investigation into Innovative Fabrication of Fiber Metal Laminated Pipe and Application. Issue 1 (March 2020) - Zijian, Lang; Meng, Zhang; Xiaoxing, Li
Abstract: Fiber reinforced metal laminated tube (FMLT) is a kind of multi-layer super-hybrid material which is cured at a fixed pressure and temperature after alternately laying metal laminated tube and fiber composite material. The development of GLARE composite pipe hydroforming technology and performance testing is of great significance to the development of aviation industry and automotive industry in terms of lightweight and safety.